UNRAVELING THE SCHNEEBERG GARNET PUZZLE: A NUMERICAL MODEL OF MULTIPLE NUCLEATION AND COALESCENCE - Dobbs H.T.; Peruzzo L.; Seno F.; Spiess R.; Prior D.J. (My University, 2003)
A quantitative kinetic model for the growth of the different garnet porphyroblast microstructures (type 1 and type 2) of the Western Schneeberg Complex (WSC) is presented. These porphyroblasts formed by a multiple nucleation and coalescence mechanism. Our numerical simulation shows that at constant diffusion rates: (1) low interface reaction rates result in a fully amalgamated porphyroblast (type 2); (2) intermediate reaction rates result in a porphyroblast, where coalescence of grains closer to the margin prevented amalgamation of those in the centre (similar to type 1 porphyroblasts); and (3) high interface reaction rates result in a porphyroblast microstructure with an atoll form. All three microstructures are characterised by distinctive cluster size distributions. A 2-D cluster size distribution analysis of type 1 porphyroblasts of WSC shows that these did not form because of intermediate interface reaction rates, but because the diffusion rate of nutrients was too low to keep pace with the interface reaction rate.